Chronic Kidney Disease and Adverse Pregnancy Outcomes: A Systematic Review and Meta-analysis. (20th October 2021) - Al Khalaf, SY; Bodunde, E; Maher, G; O'Reilly, ÉJ; McCarthy, FP; O'Shaughnessy, M; O'Neill, SM; Khashan, AS
Abstract: Objective: Chronic kidney disease (CKD) has been linked with adverse pregnancy outcomes, but few studies have examined the influence of cause and severity. The aim of this meta-analysis was to synthesize the evidence on CKD and adverse pregnancy outcome, by cause and severity of CKD where reported. Data sources: We searched PubMed, Embase, and Web of Science from inception to May 2021. Study selection and Data Extraction: Studies reporting associations between CKD and adverse pregnancy outcomes were included according to pre-defined eligibility criteria (PROSPERO protocol registration: CRD42020211925). Two reviewers independently screened titles, abstracts, and full-text articles and performed data extraction. The certainty of the evidence was assessed using the GRADE approach. Main Outcomes and Measures: We used random-effects meta-analyses to calculate pooled estimates. Primary outcomes included pre-eclampsia, Caesarean section (CS), preterm birth (PTB <37 wk.) and small for gestational age (SGA). Results: In total, 31 studies were included. The certainty of the evidence was deemed to be 'very low' for all outcomes using the GRADE approach as expected given the observational study design. Pre-pregnancy CKD was associated with pre-eclampsia [pooled adjusted odds ratio (aOR)=2.58 (1.33-5.01)], CS [aOR=1.65 (1.21-2.25)], PTB [aOR=1.73 (1.31-2.27)] and SGA [aOR= 1.93 (1.06-3.52)]. Subgroup analyses suggested that different causes of CKD had differing risks for adverse pregnancy outcomes, and later stages of CKD, compared to earlier stages, were associated with higher odds of pre-eclampsia [crude OR = 2.77 (1.73-4.44)], PTB [4.21 (2.99-5.92)], and SGA [2.43 (1.33-4.46)]. Conclusions: CKD was associated with a higher risk of adverse pregnancy outcomes, and the degree of risk varied by cause and severity. These findings highlight the need for further studies of a more robust quality evaluating the effects of cause and severity of kidney disease on adverse pregnancy outcomes. Key messages: Pre-pregnancy CKD was associated with higher risk of adverse pregnancy outcomes. The risk of adverse pregnancy outcomes varied by CKD cause and severity.